Pedagogical Assumptions Via the Internet Culture - Bilali (Halluni), Eranda; Fatmir Vadohej, Assoc. Prof. Dr.,; Mehdi Kroni, Ph. D,; Edit Lezha, Ph. D (c), (European Journal of Multidisciplinary Studies, 2016)
The pervasion of digital technology through our lives is part of a broader set of phenomena. More and more we speak now of the network society, knowledge and learning. In fact, the networks have come into our lives, permeating our daily relations with their presence. New integrations have risen between men and networks capable to create the evolution, to change the forms of our knowledge into new learning contexts. Technology makes grading easier, lesson planning easier, provides access to additional information and resources, saves time, and helps the learner expand his or her learning opportunity beyond the classroom walls (Technology in Education Consortium, 2014; Nye - McConrville, 2007). In such a learning community, teachers and students in the role of diversity, skills and participatory methods, collaborate on the construction and reconstruction of knowledge as well as the exploitation of the sense of life experiences. The interaction that the teacher assumes is the function of priority organizer of educational environments with an appropriate learning and a conscious participation. These concepts shape the basis of treatment of the paper for the presenting, authors together with their vision and generalize from contemporary literature that emphazise the role of internet culture in education
Keywords: internet, society, culture, pedagogy, education